Predictive degradation modeling with optimized interconnectors for enhancing solid oxide electrolyzer cell durability in sustainable syngas production - Abrar, Ahmad; Serene Lock, Sow Mun; Lim, Lam Ghai; Irene Lock, Sow Mei; Grazia, Leonzio; Yiin, Chung Loong; Chrisminder, Dain (Elsevier B.V., 2026)
Solid oxide electrolyzer cells offer a promising solution for sustainable syngas production via high-temperature co-electrolysis of water and CO₂. However, their long-term performance is limited by structural degradation, including cathode sintering, electrolyte phase transitions, anode delamination, and interconnector oxidation, which degrade electrochemical stability and efficiency. These degradation effects are often simplified in existing modeling studies. To address this, a material-specific degradation model was developed in Aspen Custom Modeler to simulate SOEC behavior under varying conditions. The model incorporated nickel sintering, yttria-stabilized zirconia phase changes, and interconnector oxidation. Simulation results revealed that interconnectors degrade faster, reducing the triple-phase boundary length, critical for electrochemical activity. Applying a lanthanum strontium cobaltite coating to interconnectors reduced degradation by 40.34 %, enhancing SOEC durability. These findings underscore the potential of predictive modeling combined with advanced coatings to improve SOEC performance for sustainable syngas production.